Effectiveness of the Size Matters Handwriting Program. (April 2015) - Pfeiffer, Beth; Rai, Gillian; Murray, Tammy; Brusilovskiy, Eugene
The purpose of the research was to study changes in handwriting legibility among kindergarten, first- and second-grade students in response to the Size Matters curricular-based handwriting program. A two-group pre–post-test design was implemented at two public schools with half of the classrooms assigned to receive the Size Matters program and the other continuing to receive standard instruction. All participants completed two standardized handwriting measures at pre-test and after 40 instructional sessions were completed with the classes receiving the handwriting program. Results identified significant changes in legibility in the handwriting intervention group for all three grades when compared with the standard instruction group. The results of this study support the use of a curricular-embedded handwriting program and provide the foundation for future research examining the impact of handwriting legibility on learning outcomes.